Adhesive Ability of Different Oral Pathogens to Various Dental Materials: An In Vitro Study - Yan Tu; Shuli Deng; Yuan Wang; Xiaolong Lin; Zhenyu Yang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. In dental treatments, the reason for secondary caries and the failure of root canal treatment is the microbial infection, which concerns most dentists. The challenge of how to reduce the number of bacteria at the filling materials and the number of residual bacteria in the root canal has become a research hotspot. In this study, the bacterial adhesion properties of several common dental materials were compared to provide a theoretical basis for the selection of antibacterial properties of dental materials. Methodology. Three commonly used dental restorative materials and five sealers in root canal treatment were selected. Each material block was immersed in the corresponding supragingival (Streptococcus mutans and Actinomyces viscosus) or subgingival (Porphyromonas gingivalis and Enterococcus faecalis) bacterial solution and cultured under anaerobic conditions at 37°C for 2, 4, 6, 8, 12, 16, 20, and 24 h. The adhesion of bacteria was observed, and the number of different bacteria adhering to various material model disks was calculated at different time intervals under a scanning electron microscope. The adherent CFU load of the materials was determined by colony counting. Results. Streptococcus mutans and Actinomyces viscosus exhibited the strongest adhesion ability to the resin material blocks. Porphyromonas gingivalis and Enterococcus faecalis exhibited the highest adhesion ability to the AH-Plus sealer block. Conclusions. In dental treatments, dental materials should be selected based on the chemical, physical, and biological properties of materials. In addition, it is necessary to develop new antibacterial dental materials.